2017
DOI: 10.1007/s00234-016-1769-8
|View full text |Cite
|
Sign up to set email alerts
|

Advanced MRI assessment to predict benefit of anti-programmed cell death 1 protein immunotherapy response in patients with recurrent glioblastoma

Abstract: Introduction We describe the imaging findings encountered in GBM patients receiving immune checkpoint blockade and assess the potential of quantitative MRI biomarkers to differentiate patients who derive therapeutic benefit from those who do not. Methods A retrospective analysis was performed on longitudinal MRIs obtained on recurrent GBM patients enrolled on clinical trials. Among 10 patients with analyzable data, bidirectional diameters were measured on contrast enhanced T1 (pGd-T1WI) and volumes of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 34 publications
(41 reference statements)
2
48
0
Order By: Relevance
“…Of note, ICB is known to increase the risk of oedema in patients with brain tumours, sometimes resulting in death 107,108 . This observation contrasts with the vascular normalization induced by ICB in breast cancer models 105 and suggests that the vascular effects are dependent on the tumour location and/or type — a possibility that needs to be further investigated.…”
Section: Perspectivesmentioning
confidence: 99%
“…Of note, ICB is known to increase the risk of oedema in patients with brain tumours, sometimes resulting in death 107,108 . This observation contrasts with the vascular normalization induced by ICB in breast cancer models 105 and suggests that the vascular effects are dependent on the tumour location and/or type — a possibility that needs to be further investigated.…”
Section: Perspectivesmentioning
confidence: 99%
“…This can be explained by the fact that inflammation and necrosis caused by effective treatment would lead to prominent extracellular edema and decreased cellularity. Qin et al enrolled 10 recurrent glioblastoma patients undergoing anti‐PD‐1 therapy and observed initial volumetric expansion in tumor lesion within 0‐6 months across different imaging sequences . Potential explanations for the early increase in tumor volume were continued tumor growth due to delayed responses to immunotherapy and the infiltration of inflammatory cells, which would also reduce the ADC values of the tumor lesions .…”
Section: Imaging Biomarkers For Immune Checkpoint Therapymentioning
confidence: 99%
“…Qin et al enrolled 10 recurrent glioblastoma patients undergoing anti‐PD‐1 therapy and observed initial volumetric expansion in tumor lesion within 0‐6 months across different imaging sequences . Potential explanations for the early increase in tumor volume were continued tumor growth due to delayed responses to immunotherapy and the infiltration of inflammatory cells, which would also reduce the ADC values of the tumor lesions . They found that stable or improved intermediate ADC volumes of interest (IADC VOI) after 6 months of therapy onset can provide more useful predictive information on therapeutic benefit compared with conventional imaging, including contrast‐enhanced T1‐weighted imaging (T1WI), FLAIR‐T2–weighted imaging (T2WI) and response assessment for neuro‐oncology (RANO) criteria measures …”
Section: Imaging Biomarkers For Immune Checkpoint Therapymentioning
confidence: 99%
“…Very recently, in a retrospective analysis of 10 recurrent GBM patients [98], intermediate ADC (IADC) volumes of interest (VOI) were able to discriminate the five patients with clinical benefit (i.e., without unequivocal clinical radiologic or histopathologic evidence of glioma progression for at least five months since trial onset) from the others. IADC VOI represented voxels within the FLAIR VOI having ADC in the range of highly cellular tumors (0.7–1.1 × 10 −3  mm 2 /s).…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Two are the main approaches used: (a) the histogram approach [51, 59, 65, 89, 93, 122125] in which the evolution of the tumor during therapy is completely and quantitatively characterized estimating the statistical parameters (number of peaks, kurtosis, skewness, and other statistical moments) of the distribution of the values inside the lesion and (b) the voxel-based approach [49, 50, 75, 126], which aims to detect predictive markers of therapeutic efficacy estimating voxel by voxel the difference between the parametric maps (mainly ADC, CBV, and K trans ) of two different temporal points [75] [49]. An excellent example is that recently provided by Qin et al in 2017 [98] based on an intermediate ADC (IADC) calculation in FLAIR VOI. In fact, the technique was able to discriminate patients with clinical benefit.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%